TECTONIC FRAMEWORK AND EXTENSIONAL PATTERN OF THE MALAGUIDE COMPLEX FROM SIERRA ESPUñA (INTERNAL BETIC ZONE) DURING JURASSIC–CRETACEOUS: IMPLICATIONS FOR THE WESTERNMOST TETHYS GEODYNAMIC EVOLUTION - Martín-Martín M.; Martín-Rojas I.; Caracuel J.E.; Estévez-Rubio A.; Algarra A.M.; Sandoval J. (My University, 2006)
Mapping, lithostratigraphic, biostratigraphic and structural detailed analyses in Sierra Espuña area (Internal Betic Zone, SE Spain) have allowed us to reconstruct the Jurassic–Cretaceous evolution of the Westernmost Mesomediterranean Microplate palaeomargin and, by correlation with other sectors (Northern Rift, central and western Internal Betic Zone), to propose a geodynamic evolution for the Westernmost Tethys. Extension began from Late Toarcian, when listric normal faults activated; these faults are arranged in three categories: large-scale faults, separating hectometric cortical blocks; main faults, dividing the former blocks into some kilometre-length blocks; and secondary faults, affecting the kilometric blocks. This fault ensemble, actually outcropping, in the Sierra Espuña area, broke the palaeomargin allowing the westerly Tethyan Oceanic aperture with an extension at about 17.2%. Extension was not homogeneous in time, being the Late Toarcian to the Dogger–Malm boundary the period when blocks underwent the greatest movement (rifting phase), leading to the drowning of the area (8.2% extension). During the Malm (drifting phase) extension followed (5.7%), while during the Cretaceous a change to pelagic facies is recorded with an extension of about 3.3% (post-drift stage). This evolution in the Westernmost Tethys seems to be related to areas out of the limit of significant crustal extension in the hanging wall block of the main cortical low-angle fault of the rifting.
Keywords: WESTERNMOST TETHYS OCEANIC OPENING; JURASSIC-CRETACEOUS; NORMAL FAULT CATEGORIES; EXTENSIONAL RATES; PALAEOMARGIN; Cretaceous; Toarcian; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic::Lower::Toarcian; Мезозой::Юрская::Нижний::Тоарский